THE ROLE OF VIRTUAL LEARNING PLATFORMS IN DEVELOPING CRITICAL THINKING (Marketing Journal, 2025)
his scientific article provides a theoretical and empirical analysis of the role of virtual learning environments and virtual laboratory platforms in developing studentsʼ critical thinking skills in the context of contemporary digital education . In conditions characterized by accelerated information flows and rapidly evolving knowledge , students are required not only to assimilate ready -made information but also to analyze , evaluate , compare , and formulate well-reasoned conclusions . Virtual learning platforms , particularly those incorporating laboratory simulations and problem -based tasks , create a favorable pedagogical environment for fostering critical thinking . Within the scope of the study , the didactic potential of virtual laboratories , their level of interactivity , their influence on reflective activities , and empirical outcomes are examined . Findings derived from survey data and statistical analysis indicate that systematic use of virtual laboratory platforms significantly enhances studentsʼ abilities to analyze problems , construct arguments , and make independent decisions .
Keywords: critical thinking; virtual learning platforms; virtual laboratory; empirical research; interactive learning; problem -based tasks; reflection; digital pedagogy